Consolidation of a porous limestone with nanolime - Costa, D. (2012)
This communication work reports the laboratory experiments with a nanolime product applied to the highly porous limestone currently used in Portuguese architectural heritage. The tests aimed at evaluating the short-term efficacy of the product to induce a mass consolidation effect. Other substrates were also tested for comparative purposes, namely a limestone with a different pore size distribution and a weak lime mortar. We concluded that the product has a low capability to impregnate these materials. In all cases, although at different levels, a selective migration of the product was verified, as well as an accumulation of the nanoparticles at the surface in contact with the colloidal suspension. The consolidating agent was not able to penetrate and no consolidation effect was detected in Ançã stone. On the contrary, on the two other materials, some effect could be quantified, despite the low quantity of consolidant deposited in the pores. Besides the relevant information on the potential capability to consolidate those specific substrates, the work demonstrates the advantage of using drilling resistance to evaluate the consolidation action, not only on soft and homogeneous materials but also on heterogeneous ones. In this particular case, the impregnation kinetics determined with capillary absorption tests gives a misleading information of the real performance as a consolidant. Water transfer properties and the pore size distribution were slightly changed after consolidation and require further investigation.